Couples' experiences of interacting with outside others in chronic fatigue syndrome: a qualitative study. (March 2014) - Brooks, Joanna; King, Nigel; Wearden, Alison
Objectives: Social isolation and stigma are frequently reported by patients with chronic fatigue syndrome/myalgic encephalomyelitis and relationships in the home environment with those close to the patients (their 'significant others') may thus be particularly important. Rather little attention has yet been paid to the beliefs and experiences of 'significant others' themselves in this context. This study sought to explore in-depth the beliefs and experiences of both patients and 'significant others' in relation to chronic fatigue syndrome/myalgic encephalomyelitis. Methods: In-depth interviews using a semi-structured interview schedule designed around the core constructs of the Common-Sense Model of self-regulation were conducted with two patients with chronic fatigue syndrome/myalgic encephalomyelitis and their spouses. Interpretative Phenomenological Analysis was used to analyse interview data. Results: Experiences of social interactions in relation to chronic fatigue syndrome/myalgic encephalomyelitis with others outside of the relationship dyad emerged as a key issue for all participants when reflecting on their experiences of living with the condition. These concerns are presented under two themes: interactions with healthcare professionals and interactions with the social world . Conclusions: It is evident that significant others play an important role in the lived experience of chronic fatigue syndrome/myalgic encephalomyelitis. For both patients and significant others, the wider social world and interactions with outside others may be important influences on dyadic coping in chronic fatigue syndrome/myalgic encephalomyelitis. Both future research and treatment interventions could usefully include a 'significant other' perspective.